2016
DOI: 10.51171/jms.v6i1.173
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Kejadian Arthritis Rheumatoid Pada Lansia Di Puskesmas Tompobulu Kabupaten Gowa

Abstract: Lansia pada umumnya mengalami penurunan akibat proses alamiah yaitu proses menua (aging) dengan adanya penurunan kondisi fisik, psikologis, maupun sosial yang saling berinteraksi. Arthritis rheumatoid adalah penyakit yang menyerang sendi dan struktur atau jaringan penunjang di sekitar sendi. Penderita arthritis rheumatoid di seluruh dunia telah mencapai angka 355 juta jiwa, WHO melaporkan bahwa 20% penduduk dunia terserang penyakit arthritis rheumatoid. Adapun data yang diperoleh dari Dinkes Provinsi Sulawesi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In terms of genetic factors, women are more susceptible to experiencing Rheumatoid Arthritis, especially when women enter old age. Although research conducted by Ayumar & Kasma [5] stated that there was no relationship between gender and Rheumatoid Arthritis, other similar studies stated that there was a relationship. Horiuchi et al [7] in a journal he wrote showed that the prevalence of RA patients with female sex was higher than male (p = 0.02).…”
Section: Rheumatoid Arthritis In Elderly Womenmentioning
confidence: 92%
See 1 more Smart Citation
“…In terms of genetic factors, women are more susceptible to experiencing Rheumatoid Arthritis, especially when women enter old age. Although research conducted by Ayumar & Kasma [5] stated that there was no relationship between gender and Rheumatoid Arthritis, other similar studies stated that there was a relationship. Horiuchi et al [7] in a journal he wrote showed that the prevalence of RA patients with female sex was higher than male (p = 0.02).…”
Section: Rheumatoid Arthritis In Elderly Womenmentioning
confidence: 92%
“…According to several reviewed journals, age is a factor in increasing the risk of Rheumatoid Arthritis. The results of a study conducted by Ayumar & Kasma [5] state that there is a relationship between age and the incidence of Rheumatoid Arthritis with a value of ρ (0.041) < α (0.05). Another study conducted by Pangaribuan & Olivia [6] also showed that there were more elderly respondents who had a higher level of elderly, i.e.…”
Section: Rheumatoid Arthritis In Elderly Womenmentioning
confidence: 99%